2003
DOI: 10.1177/096973300301000505
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' and Midwives' Views on Approaches to Hymen Examination

Abstract: Premarital sexual relations are unacceptable for women within Turkish society's understanding and perception of honour. If there is any suspicion about virginity, young girls are forced to undergo hymen examination against their will, which frequently results in attemped suicide. The most frequent cause of suicide in young Turkish girls is hymen examination. Nurses and midwives are always involve in this procedure. The purpose of this study was to determine the views of and approaches to hymen examination by n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 0 publications
2
23
0
2
Order By: Relevance
“…[34] Aynı fikir hemşirelik öğrencileri ve hemşirelerle yapılan çalışmada kadının evlenirken bakire olması fikrinin desteklendiği gö-rülmüştür. [17,35] Erenoğlu'nun (2008) araştırmasında, yer alan "namus, kadının evleninceye kadar bekâretini korumasıdır." önermesine erkek öğrencilerin %81.9'u, kız öğrencilerin ise %71'i katılmıştır.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…[34] Aynı fikir hemşirelik öğrencileri ve hemşirelerle yapılan çalışmada kadının evlenirken bakire olması fikrinin desteklendiği gö-rülmüştür. [17,35] Erenoğlu'nun (2008) araştırmasında, yer alan "namus, kadının evleninceye kadar bekâretini korumasıdır." önermesine erkek öğrencilerin %81.9'u, kız öğrencilerin ise %71'i katılmıştır.…”
Section: Discussionunclassified
“…Hatta çoğu gruplar ve yörelerde cinsellik içeren bir davranış sergilemesi bile onaylanmaz. [15][16][17][18] Ülkemizdeki namus kültürünün en yakıcı ve yıkıcı sonucu ise namus adına kadınlara yönelik şiddet ve namus cinayetleridir. [19][20][21] Gelişmiş ülkelerin aksine Türkiye gibi gelişmekte olan ve nüfusun çoğunluğu Müslüman olan ülkelerde, eğer kadın "namusunu" lekeler ya da kirletirse hem kendi hem de ailesinin şerefini ve onurunu zedelemiş ve namusunu lekelemiş sayılır.…”
Section: Introductionunclassified
“…9 Loss of virginity and hymen examinations appear to be a factor in a significant number of suicides of young Turkish women. 10 Such procedures have been driven by a different purpose in a number of African nations. It is reported that government ministries and a range of other organisations have advocated for, or conduct regular virginity testing on the basis that the HIV/AIDs epidemic is the result of sexually promiscuous women.…”
Section: Virginity Testingmentioning
confidence: 99%
“…Although there are several studies that have investigated Turkish peoples' premarital sexuality (e.g., Çok et al 2001;Gölbaşı and Kelleci 2011;Gürsoy and Vural 2003;Ozan et al 2005), there is still need for comprehensive studies on Turkish premarital sexual behaviors and related factors. Therefore, the purpose of this study was to investigate whether differences in social support, submissive behaviors, and loneliness exist between undergraduate students who have had sexual intercourse and those who have not.…”
mentioning
confidence: 98%